An initial study of DPMM's performance in promoting Malay enterpreneurs / Roszianah Kasim - Kasim, Roszianah (Faculty of Business and Management, 2006)
This study is to determine the promotional methods used by DPMM in promoting the interest of their members. The methods used consist of seminar, meeting, trade visit and exposition. In order to do this survey, 157 members of DPMM are selected to answer the questionnaires, but because of the lack of information and availability of time, only 36 have responded. The questionnaire constructed based on the effectiveness of promotional methods used and perception of customer towards the performance of DPMM. Data collected methods consist of primary and secondary sources. To analyze the data collected, descriptive analysis and simple correlation coefficient were used. Overall, data processing and statistical analyzing were computed by using Statistical Package Social Science (SPSS). The findings indicate that the current promotional methods used by DPMM have helped to promote members' business activities. Besides that, the relationship between the methods used and the performance of DPMM can be identified . At the end of this study, the researcher had recommended some ideas, which can help DPMM in improving their role for the member.